The Revolt of the Means. An Introductory Study, Translation, and Notes on “What is the Human Being?” by Hans-Georg Gadamer - Bey, Facundo Norberto (Anales del Seminario de Historia de la Filosofía, 2026)
This article presents the first Spanish translation of Hans-Georg Gadamer’s 1944 essay “Was ist der Mensch?” (“What is the Human Being?”), published in the Illustrierte Zeitung Leipzig in the context of the waning years of the Second World War. The introductory study situates this text, which was excluded from Gadamer’s Gesammelte Werke, within the constellation of his writings from the period and underscores its philosophical significance. Gadamer reconstructs a genealogy of Western self-understanding, from mythical-religious configurations and the Christian-Platonic synthesis to modern rationalisation and Nietzsche’s radical critique of reason. The core of his argument is that each historical response to the question of the human being -whether religious, philosophical, or technical- reveals its own one-sidedness and thereby compels the question to be reopened in the tension between the striving for totality and the awareness of finitude. This introduction presents the principal contents of the essay, with particular emphasis on Gadamer’s reflections on reason, the uprising of technical means, and the historical responsibility of philosophy.
Keywords: Gadamer; Bildung; philosophical anthropology; philosophical hermeneutics; reason; finitude; technology